WUJUD NILAI MORAL DALAM NOVEL AMIRA: CINTA DARI TANAH SURGA KARYA SULIWE - Zulfardi D (JURNAL PENDIDIKAN ROKANIA, 2020)
This research is classified as a qualitative descriptive approach to literary sociology that aims to describe the manifestation of moral values in novel Amira: Cinta dari Tanah Surga. Data sourced from novel texts that were amalyzed using moral theory. The results of the study show that the from of moral values consists of three types, namely moral values in human relations with variants of have faith, pray to God, prayer and read the Quran. Moral values in relation to humans and themselves with variants of patience, sincerity, and responsibility. Moral value of human relations with other people with variants, of advice from fellow friends, parents love children, and the love of fellow friends